I'm currently trying to understand why $|(1 + j2\pi fT)^2| = 1 + (2\pi fT)^2$ holds.

So far I have: $|(1 + j2\pi fT)^2| = |-4\pi^2 f^2T^2 + j4\pi fT + 1|$.

But why does $4\pi fT$ disappear? I know that $|j| = 1$.


For a complex number, $$|a+jb|=\sqrt{a^2+b^2}\ .$$ The easiest way in this case is $$|(1+j2\pi fT)^2|=|1+j2\pi fT|^2=1^2+(2\pi fT)^2\ .$$

  • $\begingroup$ Thanks, very simple indeed. $\endgroup$ – Zelda_CompSci Feb 17 at 23:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.